Crystal design using multipolar electrostatic interactions: A concept study for organic electronics - Peer Kirsch; Qiong Tong; Harald Untenecker (Beilstein Journal of Organic Chemistry, 2013)
Using a simple synthetic protocol, heterohexacene analogues with a quadrupolar distribution of partial charges are readily available. In contrast to most other acenes, these compounds crystallize with a slipped-stack, brickwork-like packing which is mainly controlled by electrostatic interactions. This type of packing offers an advantage for organic semiconductors, because it allows more isotropic charge transport compared to the “herring bone” stacking observed for other acenes.